One-dimensional CdS-CuS epitaxial p-n heterojunction nano material and preparation method and application thereof

By growing nanoCuS through hydrothermal reaction on the nanoCdS surface, building one-dimensional CdS-CuS epitaxial p-n heterojunction nanomaterials, the problem of low photocatalytic activity and stability of existing materials is solved, and efficient photocatalytic activity and Low-cost industrial production.

CN119259122APending Publication Date: 2025-01-07QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411412854.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing CdS-CuS p-n heterojunction materials lack tightly coupled interface and structural defects, resulting in low photocatalytic activity and stability, which cannot effectively improve photocatalytic efficiency.

Method used

By hydrothermal reaction on the nanocdS surface, a one-dimensional CdS-CuS epitaxial p-n heterojunction nanomaterial is constructed to reduce interface defects and promote electron transport. Polyvinylpyrrolidone is used as a surfactant to reduce the probability of nucleation and realize CuS epitaxial growth.

Benefits of technology

Improve the photocatalytic activity of one-dimensional CdS-CuS epitaxial p-n heterojunction nanomaterials. When used in visible photocatalytic decomposition of aquatic hydrogen production reaction, the hydrogen production rate reaches 1585.7μmol·g-1·h-1, and the process is simple and the cost is low. , suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259122A_ABST
    Figure CN119259122A_ABST
Patent Text Reader

Abstract

The invention provides a one-dimensional CdS-CuS epitaxial p-n heterojunction nano material as well as a preparation method and application thereof, and relates to the technical field of functional materials. The one-dimensional CdS-CuS epitaxial p-n heterojunction nano material provided by the invention comprises nano CdS and nano CuS which grows on the surface of the nano CdS in an epitaxial manner. In the one-dimensional CdS-CuS epitaxial p-n heterojunction nano material provided by the invention, the nano CuS epitaxially grows along the original lattice direction of the nano CdS, so that the interface defects are reduced, the effective transmission of electrons is promoted, the photocatalytic activity of the one-dimensional CdS-CuS epitaxial p-n heterojunction nano material is further improved, and when the one-dimensional CdS-CuS epitaxial p-n heterojunction nano material is applied to a reaction for producing hydrogen through visible light catalytic decomposition of water, the photocatalytic activity of the one-dimensional CdS-CuS epitaxial p-n heterojunction nano material is improved. And the highest hydrogen production rate can reach 1585.7 [mu] mol.g <-1 >. H <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, and in particular to a one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial and a preparation method and application thereof. Background Art

[0002] The rapid consumption of fossil fuels has led to increasingly serious energy shortages and environmental degradation. Photocatalytic technology can convert renewable solar energy into chemical energy and eliminate harmful substances through redox reactions, playing a very important role in the sustainable development of human society. CdS is an n-type semiconductor material with a bandgap of about 2.4eV, strong visible light absorption ability, and low conduction band potential. Therefore, it can be used to catalyze various types of photocatalytic reduction reactions. However, pure CdS will have problems such as high recombination rate of photogenerated charges and photocorrosion in photocatalytic reactions, resulting in a significant reduction in its photocatalytic activity.

[0003] The built-in electric field of the pn heterojunction can effectively drive the photogenerated electrons and holes to move in opposite directions of the heterojunction, thereby achieving spatial separation of carriers and improving photocatalytic efficiency and stability. Therefore, constructing a pn heterojunction based on CdS can effectively improve the photocatalytic activity. Among transition metal sulfides, CuS is a typical p-type semiconductor, and its bandgap is very small, which can respond well to visible light and even infrared light. The construction of a pn semiconductor heterojunction based on CdS and CuS is expected to obtain efficient photocatalytic activity. However, the current CdS-CuS pn heterojunction usually lacks a tightly coupled interface, and there are many structural defects at the interface, which greatly reduces the stability of the heterojunction and its charge separation efficiency, making the photocatalytic activity of the CdS-CuS pn heterojunction still not high enough. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial and a preparation method and application thereof. The one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial provided by the present invention has high photocatalytic activity.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a one-dimensional CdS-CuS epitaxial pn heterojunction nano material, comprising nano CdS and nano CuS epitaxially grown on the surface of the nano CdS.

[0007] The present invention provides a method for preparing the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial described in the above technical solution, comprising the following steps: mixing nano CdS, copper salt, ammonium sulfide, water and polyvinyl pyrrolidone, performing a hydrothermal reaction, epitaxially growing nano CuS on the surface of nano CdS, and obtaining the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial.

[0008] Preferably, the molar ratio of the copper element in the copper salt to the sulfur element in the ammonium sulfide is 1:1-10.

[0009] Preferably, the copper salt includes one or more of copper chloride, copper nitrate, copper acetate and copper sulfate.

[0010] Preferably, the mass ratio of the nano-CdS to polyvinyl pyrrolidone is 1:0.2-60.

[0011] Preferably, the temperature of the hydrothermal reaction is 60 to 220° C., and the time is 5 to 24 hours.

[0012] Preferably, the method for preparing nano CdS comprises the following steps:

[0013] The cadmium source, the sulfur source and ethylenediamine are mixed and subjected to a solvent thermal reaction to obtain the nano-CdS.

[0014] Preferably, the cadmium source includes one or more of cadmium acetate, cadmium nitrate, cadmium chloride and cadmium sulfate;

[0015] The sulfur source includes one or more of thioacetamide, sulfur powder and thiourea;

[0016] The molar ratio of the cadmium element in the cadmium source to the sulfur element in the sulfur source is 1:1-8;

[0017] The temperature of the solvent thermal reaction is 150-220° C. and the time is 12-24 hours.

[0018] The present invention provides the use of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial described in the above technical solution or the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared by the preparation method described in the above technical solution as a catalyst.

[0019] Preferably, the application includes application in visible light photocatalytic decomposition of water to produce hydrogen.

[0020] The present invention provides a one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial, comprising nano-CdS and nano-CuS epitaxially grown on the surface of the nano-CdS. In the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial provided by the present invention, nano-CuS grows epitaxially along the original lattice direction of nano-CdS, which reduces interface defects and promotes the effective transmission of electrons, thereby improving the photocatalytic activity of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial. When applied to the visible light catalytic decomposition of water to produce hydrogen, the hydrogen production rate can reach up to 1585.7 μmol·g -1 ·h -1 .

[0021] The present invention provides a method for preparing a one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial according to the above technical solution, comprising the following steps: mixing nano-CdS, copper salt, ammonium sulfide, water and polyvinyl pyrrolidone, performing a hydrothermal reaction, epitaxially growing nano-CuS on the surface of nano-CdS, and obtaining a one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial. The present invention epitaxially grows nano-CuS on the surface of nano-CdS by a solution method, and the nano-CuS epitaxially grows along the original lattice direction of the nano-CdS, thereby constructing a one-dimensional semiconductor single crystal CdS-CuS pn heterogeneous nanostructure with an epitaxial heterogeneous interface, thereby improving the photocatalytic activity of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial; by adding polyvinyl pyrrolidone (PVP) as a surfactant, the metal ions are coordinated and adsorbed, the nucleation supersaturation of the reaction solution is reduced, thereby reducing the homogeneous nucleation probability of the nano-CuS in the reaction solution, and promoting the epitaxial growth of the nano-CuS on the surface of the nano-CdS. Moreover, in the related art, epitaxial growth usually requires that the lattice mismatch between the two semiconductor materials to be combined meet the requirement of <5%, while the lattice mismatch between the CuS and CdS crystal planes in the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared by the present invention is as high as 18%, and the epitaxial growth of CuS can be achieved without meeting the requirement of <5% lattice mismatch.

[0022] Furthermore, the epitaxial growth of CdS-CuS pn heterojunction in the related art usually requires the use of expensive solvents and precursors, as well as harsh reaction conditions (such as reaction temperature above 250°C, vacuum or inert gas atmosphere), while the present invention does not require a very high reaction temperature (60-220°C), the reaction is carried out in water, and no expensive precursors and vacuum or inert gas protection are required. The operation is simple, the operability is strong, the cost is low, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a SEM image of the CdS nanowires prepared in Example 1;

[0024] Figure 2 This is a SEM image of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared in Example 2;

[0025] Figure 3 HRTEM image of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared in Example 2;

[0026] Figure 4 TEM image of the CuS nanoplate prepared in Comparative Example 1;

[0027] Figure 5 XRD patterns of the CdS nanowires prepared in Example 1, the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterials prepared in Example 2, and the CuS nanoplates prepared in Comparative Example 1;

[0028] Figure 6 This is a SEM image of the non-epitaxial CdS / CuS composite prepared in Comparative Example 2;

[0029] Figure 7 This is a comparison chart of the activity of photolysis of water to produce hydrogen. DETAILED DESCRIPTION

[0030] The present invention provides a one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial, comprising nano-CdS and nano-CuS epitaxially grown on the surface of the nano-CdS. In the present invention, the nano-CdS may include CdS nanowires and / or CdS nanorods; the nano-CuS may be a CuS nanoplate. In the present invention, the epitaxial growth may be that the nano-CuS grows vertically on the surface of the nano-CdS. In a specific embodiment, the epitaxial growth may be that the CuS nanoplate grows vertically on the side of the nano-CdS. In the present invention, the lattice spacing of the nano-CuS may be 0.278nm; the lattice spacing of the nano-CdS may be 0.339nm.

[0031] In the present invention, the aspect ratio of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial can be ≥ 5. The one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial provided by the present invention has a large aspect ratio, provides a fast transmission and separation channel for photogenerated charges, and is conducive to improving the photocatalytic activity of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial.

[0032] The present invention provides a method for preparing the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial described in the above technical solution, comprising the following steps: mixing nano-CdS, copper salt, ammonium sulfide, water and polyvinyl pyrrolidone (referred to as the first mixing), performing a hydrothermal reaction, epitaxially growing nano-CuS on the surface of nano-CdS, and obtaining the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial.

[0033] Unless otherwise specified, the materials used in the present invention are all commercially available products in the art.

[0034] In the present invention, the method for preparing the nano-CdS may include the following steps: mixing a cadmium source, a sulfur source and ethylenediamine (referred to as the second mixing), and performing a solvothermal reaction to obtain the nano-CdS.

[0035] In the present invention, the cadmium source may include one or more of cadmium acetate, cadmium nitrate, cadmium chloride and cadmium sulfate, and the cadmium nitrate may be cadmium nitrate hexahydrate. In the present invention, the sulfur source may include one or more of thioacetamide, sulfur and thiourea, and the sulfur may be sulfur powder and / or sublimated sulfur. In the present invention, the molar ratio of the cadmium element in the cadmium source to the sulfur element in the sulfur source may be 1:1 to 8. In a specific embodiment, the molar ratio of the cadmium element in the cadmium source to the sulfur element in the sulfur source may be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 or 1:8. In the present invention, the ratio of the mass of the cadmium source to the volume of ethylenediamine can be 1g:15-200mL. In a specific embodiment, the ratio of the mass of the cadmium source to the volume of ethylenediamine can be 1g:15mL, 1g:50mL, 1g:60mL, 1g:80mL, 1g:100mL, 1g:125mL, 1g:150mL or 1g:200mL.

[0036] In the present invention, the second mixing can be stirring mixing; the time of the second mixing can be 20 to 90 minutes, and in a specific embodiment, the time of the second mixing can be 20 minutes, 25 minutes, 30 minutes, 40 minutes, 60 minutes, 80 minutes or 90 minutes. In the present invention, the temperature of the solvent thermal reaction can be 150 to 220 degrees Celsius, and in a specific embodiment, the temperature of the solvent thermal reaction can be 150 degrees Celsius, 160 degrees Celsius, 170 degrees Celsius, 180 degrees Celsius, 190 degrees Celsius, 200 degrees Celsius, 210 degrees Celsius or 220 degrees Celsius; the time of the solvent thermal reaction can be 12 to 24 hours, and in a specific embodiment, the time of the solvent thermal reaction can be 12 hours, 14 hours, 15 hours, 16 hours, 18 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours. The present invention does not specifically limit the pressure of the solvent thermal reaction, and in a specific embodiment, the pressure of the solvent thermal reaction can be the pressure inside the reaction container.

[0037] After completing the solvothermal reaction, the present invention can also wash and dry the solvothermal product obtained by the solvothermal reaction. In the present invention, the washing can include washing with a polar organic solvent, and the polar organic solvent can be ethanol; the number of washings can be 3 to 5 times, and in a specific embodiment, the number of washings can be 3 times, 4 times or 5 times. The present invention washes away the ethylenediamine adsorbed on the surface of the solvothermal product by washing with a polar organic solvent. In the present invention, the drying can include drying; the drying temperature can be 50 to 80°C, and in a specific embodiment, the drying temperature can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C. The present invention does not specifically limit the drying time, and the solid obtained by the washing can be dried to a constant weight.

[0038] In the present invention, the copper salt may include one or more of copper chloride, copper nitrate, copper acetate and copper sulfate. In the present invention, the molar ratio of the copper element in the copper salt to the sulfur element in ammonium sulfide may be 1:1-10. In a specific embodiment, the molar ratio of the copper element in the copper salt to the sulfur element in ammonium sulfide may be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10.

[0039] In the present invention, the mass ratio of the nano CdS to polyvinyl pyrrolidone can be 1:0.2-60. In a specific embodiment, the mass ratio of the nano CdS to polyvinyl pyrrolidone can be 1:0.2, 1:1, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:50 or 1:60.

[0040] In the present invention, the ratio of the mass of the nano-CdS to the volume of water can be 1g:60-3000mL. In a specific embodiment, the ratio of the mass of the nano-CdS to the volume of water can be 1g:60mL, 1g:200mL, 1g:500mL, 1g:600mL, 1g:1000mL, 1g:1500mL, 1g:2000mL, 1g:2500mL or 1g:3000mL.

[0041] In the present invention, the mixing of nano-CdS, copper salt, ammonium sulfide, water and polyvinyl pyrrolidone may include: mixing nano-CdS and water for the third time, mixing with copper salt and polyvinyl pyrrolidone for the fourth time, and finally mixing with ammonium sulfide for the fifth time. In the present invention, the third mixing, the fourth mixing and the fifth mixing may be independently stirring mixing; the fifth mixing time may be 30 to 60 minutes, and in a specific embodiment, the fifth mixing time may be 30 minutes, 35 minutes, 40 minutes, 50 minutes or 60 minutes.

[0042] In the present invention, the temperature of the hydrothermal reaction can be 60-220°C. In a specific embodiment, the temperature of the hydrothermal reaction can be 60°C, 80°C, 100°C, 120°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C. The time of the hydrothermal reaction can be 5-24h. In a specific embodiment, the time of the hydrothermal reaction can be 5h, 6h, 8h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 18h, 20h, 21h, 23h or 24h. The present invention does not specifically limit the pressure of the hydrothermal reaction. In a specific embodiment, the pressure of the hydrothermal reaction can be the pressure inside the reaction vessel.

[0043] After completing the hydrothermal reaction, the present invention can also wash the hydrothermal product obtained by the hydrothermal reaction with alcohol and then dry it. In the present invention, the alcohol can include ethanol; the number of alcohol washings can be 3 to 5 times, and in a specific embodiment, the number of alcohol washings can be 3 times. In the present invention, the drying can include vacuum drying; the drying temperature can be 60°C. The present invention does not specifically limit the drying time, and the solid obtained by the alcohol washing can be dried to a constant weight.

[0044] The present invention provides the use of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial described in the above technical solution or the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared by the preparation method described in the above technical solution as a catalyst. In the present invention, the application may include the application in the visible light catalytic decomposition of water to produce hydrogen reaction. The one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial provided by the present invention has excellent photocatalytic activity. When used in the visible light catalytic decomposition of water to produce hydrogen reaction, the hydrogen production rate can reach up to 1585.7μmol·g -1 ·h -1 .

[0045] In order to further illustrate the present invention, a one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial provided by the present invention and its preparation method and application are described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0046] Example 1

[0047] 0.6169 g of cadmium nitrate hexahydrate and 0.12828 g of sublimed sulfur were added to 35 mL of ethylenediamine, mixed under ultrasonic stirring at room temperature for 20 min to fully dissolve them, and then transferred to a 100 mL high-pressure reactor and subjected to solvothermal reaction at 200 °C for 12 h. After the reaction, the solvothermal reaction product was washed three times with ethanol in a 50 mL centrifuge tube and dried in vacuum at 60 °C to obtain CdS nanowires.

[0048] Figure 1 The SEM (scanning electron microscope) image of the CdS nanowires prepared in Example 1 is shown in FIG. Figure 1 It can be seen that the obtained CdS product is regular nanowires.

[0049] Example 2

[0050] 0.05 g of the CdS nanowires prepared in Example 1 were dispersed in 30 mL of deionized water to obtain a CdS nanowire suspension. 0.059 g of copper chloride and 2 g of polyvinyl pyrrolidone were added to the CdS nanowire suspension, stirred until the copper chloride and polyvinyl pyrrolidone were dissolved, and then 0.347 mL of a 20 wt% aqueous solution of ammonium sulfide was added, stirred and mixed for 30 min, and then transferred to a 50 mL autoclave for hydrothermal reaction at 180° C. for 12 h. After the reaction was completed, the hydrothermal reaction product was washed with ethanol for 3 times and vacuum dried at 60° C. to obtain a one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial.

[0051] Figure 2 This is a SEM image of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared in Example 2. Figure 2 It can be seen that the CuS nanoplates grow vertically onto the CdS nanowires.

[0052] Figure 3 This is a HRTEM (high resolution transmission electron microscope) image of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared in Example 2. Figure 3 It can be seen that the CuS nanoplates grow vertically onto the CdS nanowires; in addition, the nanoplates and nanowires show lattice spacings of 0.278nm and 0.339nm, respectively, which can be attributed to the (006) crystal plane of hexagonal CuS and the (002) crystal plane of wurtzite CdS, respectively. After calculation, it is found that the lattice mismatch between these two crystal planes is as high as 18%.

[0053] Comparative Example 1

[0054] 0.085 g of copper chloride and 2 g of polyvinyl pyrrolidone were added to 30 mL of deionized water and stirred to dissolve to obtain a copper chloride solution. Then, 0.5 mL of a 20 wt% ammonium sulfide aqueous solution was added to the copper chloride solution, stirred evenly, and then transferred to a 50 mL autoclave for hydrothermal reaction at 180° C. for 12 h. After the reaction was completed, the hydrothermal reaction product was washed with ethanol for 3 times and vacuum dried at 60° C. to obtain a CuS nanoplate.

[0055] Figure 4 TEM (transmission electron microscope) image of the CuS nanoplate prepared in Comparative Example 1. Figure 4 It can be seen that the CuS product is a regular hexagonal nanoplate.

[0056] XRD (X-ray diffraction) tests were performed on the CdS nanowires prepared in Example 1, the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterials prepared in Example 2, and the CuS nanoplates prepared in Comparative Example 1. Figure 5 Their XRD patterns are shown in Figure 2. Figure 5 It can be seen that the diffraction peaks of CdS nanowires and CuS nanoplates match those of wurtzite CdS (JCPDS Card No. 77-2306) and hexagonal CuS (JCPDS Card No. 78-2121), respectively, and the XRD spectrum of the CdS-CuS composite sample contains the characteristic diffraction peaks of CdS and CuS, indicating the successful preparation of one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterials.

[0057] Comparative Example 2

[0058] 0.05 g of the CdS nanowires prepared in Example 1 were dispersed in 30 mL of deionized water to obtain a CdS nanowire suspension. 0.059 g of cupric chloride was added to the CdS nanowire suspension, stirred until the cupric chloride was dissolved, and then 0.347 mL of a 20 wt% aqueous solution of ammonium sulfide was added, stirred and mixed for 30 min, and then transferred to a 50 mL autoclave for hydrothermal reaction at 180° C. for 12 h. After the reaction was completed, the hydrothermal reaction product was washed with ethanol for 3 times and vacuum dried at 60° C. to obtain a non-epitaxial CdS / CuS composite.

[0059] Figure 6 This is a SEM image of the non-epitaxial CdS / CuS composite prepared in Comparative Example 2. Figure 6 It can be seen that in the absence of PVP, CuS nanoplates cannot grow onto CdS nanowires in an epitaxial manner.

[0060] Test Example 1

[0061] The CdS nanowires prepared in Example 1, the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterials prepared in Example 2, the CuS nanoplates prepared in Comparative Example 1, and the non-epitaxial CdS / CuS composites prepared in Comparative Example 2 were used as catalysts to test the performance of photocatalytic water splitting and hydrogen production. The test method is as follows:

[0062] 10 mg of the catalyst was ultrasonically dispersed in 100 mL of an aqueous solution containing 8.4 g of sodium sulfide nonahydrate and 3.15 g of anhydrous sodium sulfite to obtain a suspension. The suspension was then transferred to a reaction device, and the air dissolved in the suspension was discharged by a vacuum pump. Visible light was used for irradiation, and the light source was a 300 W xenon lamp equipped with a 420 nm cutoff filter. A constant temperature circulating water pump was used to control the reaction temperature to 10 ° C. Every 30 minutes, the precipitated hydrogen was detected using a GC-2014C gas chromatograph. The results are as follows: Figure 7 shown.

[0063] Figure 7 The figure is a comparison chart of the activity of photolysis of water to produce hydrogen, wherein the legends from top to bottom are CdS-CuS (one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared in Example 2), CdS / CuS (non-epitaxial CdS / CuS composite prepared in Comparative Example 2), CdS (CdS nanowire prepared in Example 1) and CuS (CuS nanoplate prepared in Comparative Example 1). Figure 7 It can be seen that compared with the CdS nanowires prepared in Example 1, the CuS nanoplates prepared in Comparative Example 1 and the non-epitaxial CdS / CuS composite prepared in Comparative Example 2, the photocatalytic hydrogen production activity of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared in Example 2 is significantly improved, reaching 1585.7 μmol·g -1 ·h -1 .

[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial, comprising nano-CdS and nano-CuS epitaxially grown on the surface of the nano-CdS.

2. The method for preparing the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial according to claim 1, characterized in that: The following steps are involved: Nano-CdS, copper salt, ammonium sulfide, water and polyvinyl pyrrolidone are mixed and subjected to hydrothermal reaction, and nano-CuS is epitaxially grown on the surface of nano-CdS to obtain a one-dimensional CdS-CuS epitaxial pn heterojunction nano-material.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the copper element in the copper salt to the sulfur element in the ammonium sulfide is 1:1-10.

4. The preparation method according to claim 2 or 3, characterized in that: The copper salt includes one or more of copper chloride, copper nitrate, copper acetate and copper sulfate.

5. The preparation method according to claim 2, characterized in that: The mass ratio of the nano CdS to polyvinyl pyrrolidone is 1:0.2-60.

6. The preparation method according to claim 2, 3 or 5, characterized in that: The temperature of the hydrothermal reaction is 60 to 220° C., and the time is 5 to 24 hours.

7. The preparation method according to claim 2, characterized in that: The preparation method of the nano CdS comprises the following steps: The cadmium source, the sulfur source and ethylenediamine are mixed and subjected to a solvent thermal reaction to obtain the nano-CdS.

8. The preparation method according to claim 7, characterized in that: The cadmium source includes one or more of cadmium acetate, cadmium nitrate, cadmium chloride and cadmium sulfate; The sulfur source includes one or more of thioacetamide, sulfur powder and thiourea; The molar ratio of the cadmium element in the cadmium source to the sulfur element in the sulfur source is 1:1-8; The temperature of the solvent thermal reaction is 150-220° C. and the time is 12-24 hours.

9. Use of the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial according to claim 1 or the one-dimensional CdS-CuS epitaxial pn heterojunction nanomaterial prepared by the preparation method according to any one of claims 2 to 8 as a catalyst.

10. The use according to claim 9, characterized in that: The application includes application in visible light photocatalytic decomposition of water to produce hydrogen.